Internationalisation of Higher Education in Latin America and the Caribbean:: In Need of Robust Policies - Gacel-Ávila, Jocelyne (International Journal of African Higher Education, 2020)
This article assesses the current process of internationalisation of higher education in Latin America and the Caribbean. Based on data and findings from different national, regional and international studies, it shows that, while the region’s primary form of internationalisation is student mobility, the numbers are relatively small compared to other regions and that other strategies such as internationalisation at home are largely underdeveloped. The article concludes that, while some progress has been made in past decades, the internationalisation process needs to be consolidated and strengthened, particularly in terms of public policy at national and regional level.